FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA CARPAL TUNNEL SYNDROME PADA PEKERJA OJEK ONLINE DI KOTA DENPASAR - Paramita, I Gusti Agung Vina; Wirawan, I Made Ady (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT Occupational diseases are diseases caused by work, work tools, materials, processes and work environment. One of the frequently reported occupational diseases is musculoskeletal. One type of MSDs is Carpal Tunnel Syndrome. Carpal Tunnel Syndrome is a disorder of the body parts of the hand that causes pain and numbness, especially in the thumb and three main fingers, namely the index finger, middle finger and some of the ring finger. Online motorcycle taxi is a job that has a risk of Carpal Tunnel Syndrome. This study aims to determine the factors that influence the occurrence of Carpal Tunnel Syndrome. This research is an analytical research with a quantitative approach using the cross-sectional study method with a total sample of 80 respondents and was carried out in May-June 2023. The variables observed were individual variables consisting of age and gender, as well as occupational variables consisting of length of work, duration of work, hand posture and use of personal protective equipment. The results of the analysis using the chi-square test showed that the variables that had a relationship with Carpal Tunnel Syndrome were age (p=0.00), years of service (p=0.04), and hand posture (p=0.00). the results of multivariable analysis showed that age and hand posture had the most significant relationship with the incidence of CTS. Keywords: Occupational Diseases, Carpal Tunnel Syndrome, Ojek Online